Design with Uncertainty: The Role of Future Options for Infrastructure Integration. (26th July 2016) - Martani, Claudio; Jin, Ying; Soga, Kenichi; Scholtes, Stefan
Abstract: Decision making for effective infrastructure integration is challenging because the performance of long‐lasting facilities is often difficult to foresee or well beyond the designer's control. We propose a new approach for integrating the construction/retrofitting of two or more types of facilities. Infrastructure integration has many perceived benefits, but practitioners also express serious doubts, particularly when it comes to civil engineering works. To substantiate this approach, we test all of the major options for integrating a ground source heat pump system with the construction/retrofitting of an archetypal office building. We use actual data from the United Kingdom, which represent a middle‐of‐the‐road setting among major developed countries. The model highlights the sensitivity of the range of cost‐effective solutions to the embedding of future options. The findings point to a clear need for appropriate standards for managing infrastructure integration. We expect this kind of model to find increasing applications among infrastructure complexes, particularly as cities become denser and more multifunctional.